Evaluation design for the environmental and natural resource management project in Malawi - Coen, Thomas; Mamun, Arif; Ringler, Claudia; Nkonya, Ephraim M.; Velyvis, Kristen; Xie, Hua; Powell, Helen; Brecher-Haimson, Jeremy; Dumitrescu, Anca; Sloan, Matt (Mathematica Policy Research, 2020)
Malawi generates 98 percent of its electricity from hydropower, relying primarily on three power plant sites along the Shire River. However, the rapid growth of invasive aquatic weeds limits the free flow of water in the river, leading to costly blockages and breakdowns that interrupt the power supply and reduce generative capacity (Government of Malawi 2013; Lea and Hanmer 2009). Excessive sedimentation in the Shire River reduces active storage at hydropower plants, hindering the ability of plant operators to optimize plant production. Mechanical removal of weeds and dredging of sediment around dams and in head ponds should dramatically improve water flow in the short term, but longer term solutions likely entail engaging upstream communities in improved agricultural and environmental practices that focus on preventing environmental degradation, soil erosion, and fertilizer runoff (United Nations Environment Programme 2013). Economic poverty, population density, and a lack of suitable agricultural land, especially in the Shire River catchment area, have prompted households to cultivate in fragile areas, on steep slopes, and along river banks, creating a challenge for households to change land management practices. Economic poverty is also a cause of deforestation as communities cut down trees for economic gain from charcoal production, meeting the market demand of urban dwellers (Government of Malawi 2013).